2015
DOI: 10.1111/imm.12485
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer T cells in multiple sclerosis and its animal model, experimental autoimmune encephalomyelitis

Abstract: SummaryMultiple sclerosis (MS) is a chronic inflammatory disease that causes demyelination of neurons in the central nervous system. Traditional therapies for MS have involved anti-inflammatory and immunosuppressive drugs with significant side effects that often only provide short-term relief. A more desirable outcome of immunotherapy would be to protect against disease before its clinical manifestation or to halt disease after its initiation. One attractive approach to accomplish this goal would be to restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 98 publications
0
28
0
Order By: Relevance
“…In diabetes-prone NOD animals, for instance, frequencies of iNKT cells are reduced, and challenge with aGalCer protects against disease (22). Although studies of animals models of multiple sclerosis and rheumatoid arthritis have produced conflicting results with regard to the role of iNKT cells in these diseases, studies of patients revealed reductions in the frequency and function of iNKT cells that were similar to those observed with other autoimmune diseases (23,24).…”
mentioning
confidence: 88%
“…In diabetes-prone NOD animals, for instance, frequencies of iNKT cells are reduced, and challenge with aGalCer protects against disease (22). Although studies of animals models of multiple sclerosis and rheumatoid arthritis have produced conflicting results with regard to the role of iNKT cells in these diseases, studies of patients revealed reductions in the frequency and function of iNKT cells that were similar to those observed with other autoimmune diseases (23,24).…”
mentioning
confidence: 88%
“…Following activation of iNKT cells (via binding to α-GalCer-CD1d complex) an array of cytokines is secreted that are associated with both pro-and anti-inflammatory immune responses and play a role in both innate and acquired immunity. As such, iNKT cells, (i) secrete interleukin (IL)-4 and IL-13 which stimulate CD4 + T cells to differentiate into anti-inflammatory Th2 cells (IL-4, IL-10 producers) which inhibit Th17, Th1, CD8 + T cells in the CNS; (ii) secrete IL-2 and tumor growth factor (TGF)-beta which stimulate the production of T regulatory (Treg) cells (IL-10, TGF-beta producers) which inhibit Th17, Th1 and CD8 + T cells in the CNS; and (iii) secrete IL-4, IL-10, IL-13, interferon (IFN)-gamma and GM-CSF which activate suppressive myeloid derived suppressor cells (MDCs), DC and macrophages which in turn secrete IL-10 to activate Treg cells and suppress Th17, Th1 and CD8 + T cells in the CNS [32]. Due to the pleiotropic properties of iNKT cells, they play a role in protecting the host against pathogens, tumors, autoimmunity and are involved in tissue rejection, ischemia reperfusion injury and obesity related diabetes [32]; deficiency or dysfunction of iNKT cells has been shown to be linked to the development of autoimmune diseases.…”
Section: Natural Killer T (Nkt) Cellsmentioning
confidence: 99%
“…Due to the pleiotropic properties of iNKT cells, they play a role in protecting the host against pathogens, tumors, autoimmunity and are involved in tissue rejection, ischemia reperfusion injury and obesity related diabetes [32]; deficiency or dysfunction of iNKT cells has been shown to be linked to the development of autoimmune diseases. Indeed, iNKT cell numbers are decreased in patients with MS [32] and are restored in patients in remission [33]. Analysis of iNKT cells in MS patients in remission showed a Th2 cytokine profile, suggesting an immunoregulatory effect of iNKT cells in MS [34].…”
Section: Natural Killer T (Nkt) Cellsmentioning
confidence: 99%
“…Many of these studies have been performed with the prototypical iNKT cell antigen α-galactosylceramide (α-GalCer), a potent iNKT cell agonist that was originally isolated from a marine sponge ( 28 ). α-GalCer and related glycolipids have potent anti-metastatic activities ( 29 ), hasten clearance of some microbial pathogens ( 3 5 ), enhance the efficacy of vaccines ( 30 , 31 ), prevent graft-vs.-host disease ( 21 ), and protect against autoimmunity in experimental models for type 1 diabetes ( 32 ), multiple sclerosis ( 33 ), arthritis ( 34 ), and systemic lupus erythematosus ( 35 ).…”
Section: General Properties and Functions Of Inkt Cellsmentioning
confidence: 99%